2010
DOI: 10.1007/s13187-010-0172-0
|View full text |Cite
|
Sign up to set email alerts
|

The Attitude of Oncology Physicians and Nurses to the Acceptance of New Drugs for Gene Therapy

Abstract: With the efficacy of gene therapy verified in phase III trials, cancer patients will consider whether to accept gene therapy sooner or later. The purpose of this study is to investigate the attitudes of oncology physicians and nurses regarding effective gene therapy. A questionnaire was administered to 368 oncology physicians and nurses. A total of 328 valid questionnaires were returned (response rate, 89.1%). Gene therapy was considered as very safe or safe by 256 (78.0%) participants. Regardless of the stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…39,40,42,47,51,[53][54][55]62,63 The impact of career was mixed, with four studies finding that science-oriented careers were a significant predictor of greater levels of acceptance of gene therapy, 29,31,35,62 while six studies found little to no relationship. 33,43,48,52,53,66 In a recent study, Ganne et al also reported no difference in the acceptance of genetic research among eye care professionals, optometry students, and the general public, reporting an average 70% approval rate across all three samples. 52 Self-reported and tested knowledge of genetics was found to positively impact the acceptance of gene therapy.…”
Section: Knowledge/educationmentioning
confidence: 99%
See 3 more Smart Citations
“…39,40,42,47,51,[53][54][55]62,63 The impact of career was mixed, with four studies finding that science-oriented careers were a significant predictor of greater levels of acceptance of gene therapy, 29,31,35,62 while six studies found little to no relationship. 33,43,48,52,53,66 In a recent study, Ganne et al also reported no difference in the acceptance of genetic research among eye care professionals, optometry students, and the general public, reporting an average 70% approval rate across all three samples. 52 Self-reported and tested knowledge of genetics was found to positively impact the acceptance of gene therapy.…”
Section: Knowledge/educationmentioning
confidence: 99%
“…62 Participants in the studies were from a range of sources, including participants involved in gene therapy trials, 32 international samples, 30,47,55,57 national samples, 18,39,40,42,43,60,[62][63][64][65]67 people recruited from the general public, 34,35,38,51,52,59,63 students, 33,38,45,49,52,53,56 conference or public scientific engagement event attendees, 35,58,59,66 teachers, 54 patients, [36][37][38]41,44,46,61 parents of children with a disease, 19,38 and health practitioners. 36,46,48,52 Five of the studies utilized online...…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The safety of gene therapy is an important issue that participants and medical staff must consider [38]. One of the major concerns in gene therapy is the possibility of infectious transmission of recombinant genes with viral vectors [39].…”
Section: Safetymentioning
confidence: 99%